2000
DOI: 10.1038/sj.onc.1204019
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced tumorigenicity caused by truncation of the extracellular domain of GP125/CD98 heavy chain

Abstract: GP125/CD98 is a heterodimeric 125-kDa glycoprotein, which consists of an 85-kDa heavy chain (hc) and a 40-kDa light chain (lc), and is strongly expressed on the cell surface of various tumor cells, irrespective of their tissue of origin. We have recently demonstrated that overexpression of the CD98hc cDNA causes malignant transformation of NIH3T3 cells. To investigate the function of the extracellular domain of CD98hc in cell proliferation and malignant transformation, we established two NIH3T3-derived clones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
40
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 53 publications
2
40
0
Order By: Relevance
“…It has been shown previously that 4F2 overexpression in NIH 3T3 cells results in changes consistent with malignant transformation 17,20 and monoclonal antibodies against 4F2 have been shown to inhibit tumor cell nucleic acid synthesis and proliferation of several cell types. 21,22 The malignant alterations, however, required association with the CD98 complex light chain.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…It has been shown previously that 4F2 overexpression in NIH 3T3 cells results in changes consistent with malignant transformation 17,20 and monoclonal antibodies against 4F2 have been shown to inhibit tumor cell nucleic acid synthesis and proliferation of several cell types. 21,22 The malignant alterations, however, required association with the CD98 complex light chain.…”
mentioning
confidence: 85%
“…[8][9][10][11][12][13] The glycoprotein-associated transporters are a novel class of amino acid transporters recently the subject of much interest not only in relation to transport but also to CD98-linked functions in cell activation, integrin signaling, cell fusion and malignant transformation. [14][15][16][17] Our research has utilized a tetracycline-inducible adenoviral expression system (TET-Off) system to alter levels of LAT1 and 4F2 in vitro. We have increased LAT1 expression in normal hepatic cells to determine functional changes occurring in processes associated with cancer.…”
mentioning
confidence: 99%
“…Stable NIH3T3 transfectant clones expressing full-length human CD98hc protein (NIH/hH-1, NIH/hH-2 and NIH/hH-3) and a control NIH3T3 transfectant clone (NIH/neo) were maintained in DMEM containing 10% FBS and 400 lg/mL of Geneticin disulfate (G418; Wako Pure Chemical Industries, Osaka, Japan). (31,33) Multiple aliquots of individual clones (passages 5-10) were frozen, and each aliquot was used for no more than 2 weeks, to avoid potential phenotypic changes. Expression of human CD98hc protein on the cell surface of each clone was confirmed periodically by flow cytometry, as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…Several groups report the higher expression of CD98 in restricted normal tissues, which contain actively dividing cells. (1,2,(21)(22)(23)(24)(25) As to the involvement of CD98 in cancers, we have reported higher expression of CD98 in various cancer cells using specific anti-CD98hc mAb, (2,26) growth inhibition of cancer cells by anti-CD98hc mAb (27)(28)(29) or by liposomes containing anticancer drug and coated with anti-CD98hc mAb, (30) malignant transformation of mouse fibroblasts by DNA transfection of human and rat cDNA of CD98hc, (31)(32)(33) and cooperation between CD98hc and CD98lc in the malignant transformation. (32) We have recently demonstrated that the CD98lc responsible for CD98hc-mediated malignant transformation is L-type amino-acid transporter 1 (LAT1), also referred to as solute carrier (SLC) 7A5, among six CD98lc, namely, LAT1, LAT2 (SLC7A8), y+LAT1 (SLC7A7), y+LAT2 (SLC7A6), asc1 (SLC7A10) and xCT (SLC7A11), from experimental genetics using LAT1 gene-disrupted chicken DT40 cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation